A systematic review of bone graft products used in lumbar interbody fusion procedures for degenerative disc disease - Anita Fitzgerald, MPH; Rachael McCool, BSc; Emma Carr, BA; Paul Miller, MSc; Katie Reddish, BSc; Cynthia C Lohr, DC; Elena Annoni, MSc; Brandon Lawrence, MD (North American Spine Society Journal)
Background: Degenerative disc disease (DDD) is associated with chronic lower back pain that may have impacts on individual's quality of life and functional ability. Lumbar interbody fusion can be carried out with a variety of bone grafting products, the choice depends on several factors including the patient, site, procedure, cost and indication. This systematic review (SR) intends to validate and consolidate the existing evidence base supporting bone graft materials related to lumbar interbody fusion procedures for DDD, specifically anterior lumbar interbody fusion (ALIF) and oblique lumbar interbody fusion (OLIF). Methods: An SR was conducted in February 2023. Clinical and economic studies of adults with DDD in regions L2 to S1 undergoing lumbar interbody fusion with Infuse™, allograft, synthetic bone grafts, demineralized bone matrices or cell-based matrices were eligible for inclusion. Results: Twenty-one studies (reported in 25 publications) were included in the review. Eighteen studies (reported in 22 publications) reported clinical outcomes, while 4 studies reported economic outcomes. Nine studies (in 5 publications) investigated Infuse™, including 3 randomized controlled trials (RCTs), one cohort study and 4 case series. Ten studies investigated allograft bone, bone harvested from the vertebral spur combined with apacerum powder, or tricalcium phosphate soaked in autologous bone marrow aspirate, including one RCT, 2 cohort studies, and 7 case series. Conclusions: The SR shows that Infuse™ offers comparable results to iliac crest bone graft with the benefit of not requiring harvested bone and offers significant benefits in surgical time and blood loss. There is a lack of comparative evidence for any other bone grafts identified in this SR, highlighting the need for further well-designed studies to be conducted in this area.